History and fiction in the polyphonic novel by António Lobo Antunes - Fornos, José Luis Giovanoni (2012)
This essay discusses the relationship between history and fiction, considering the positions of the French philosopher Paul Ricoeur. An overview of the fictional universe of the Portuguese writer António Lobo Antunes is provided, calling attention to the importance of polyphony as a theoretical increase in the understanding of history and literature. The official history of Portugal is examined in the light of narrative strategies employed by the social voices of Antunes’ novels.